Factors associated with utilization of mobile health clinic hepatitis C virus services among medically underserved communities in South Carolina - Kerry A. Howard; Fatih Gezer; Caitlin A. Moore; Brian Witrick; Abass Babatunde; Prerana Roth; Ashley Coleman; Kristie Boswell; Ronald W. Gimbel; Alain H. Litwin; Lior Rennert (BMC Global and Public Health)
Abstract Background Mobile health clinics (MHCs) are effective mechanisms for hepatitis C virus (HCV) screening and treatment in underserved populations. However, effective strategies for identifying and prioritizing high-risk communities are lacking. This study examined individual-level and community-level predictors of MHC utilization, HCV positivity rates, and HCV treatment initiation to assess the utility of these programs and improve MHC allocation. Method Clemson Rural Health (CRH), a health service delivery organization focused on rural and underserved communities, mobilizes MHCs for HCV screening and treatment initiation in the Upstate and Midlands regions of South Carolina. Participants for this study were individuals screened at CRH MHC sites between May 2021 and January 2024. Generalized linear mixed-effects models were used to examine the association between community-level predictors and number of individuals screened and community- and individual-level predictors and infection status and treatment initiation. Results The community-level analysis showed that individuals from census tracts with higher rates of poverty (relative risk; RR = 1.32, p = .012), higher rates of uninsurance (RR = 1.31, p = .003), and less rural areas (RR = 0.74, p = .029) were more likely to utilize the MHC for HCV screening. The individual-level analysis showed that an individual’s age of 30–44 (RR = 2.28, p = .020), non-White race (RR = 0.32, p < .001), history of injection drug use (RR = 10.16, p < .001), and lack of insurance (RR = 1.99, p < .001) were significantly associated with infection status. Lack of insurance (RR = 2.67, p = .012) was the only individual-level factor associated with treatment initiation. Community-level factors associated with treatment initiation were higher rates of poverty (RR = 1.72, p = .027) and uninsurance (RR = 1.74, p = .023), while a greater percent of individuals ages 30–44 was associated with less treatment initiation (RR = 0.47, p = .028). Conclusions While programs and protocols for care for difficult-to-treat populations exist, understanding the effectiveness for uptake among target populations is necessary. The study demonstrated the utilization of MHC HCV services by the individuals and communities that would most benefit from this type of care. Screening services were utilized more by communities that tend to be medically underserved, and HCV infections were identified in groups that are known to be at high risk. Going forward, these findings can be used to direct allocation of MHC HCV resources for targeted intervention.